GERMÁN HERNÁNDEZ AMORES: APORTACIONES ICONOGRÁFICAS - Ramallo Asensio, Germán (Imafronte, 1994)
An analysis is made of the painting entitled Journey of the Virgin and St. John to Ephesus after the death of the Redeemer (the Boat) and the conclusion reached that it could, in fact, be an intellectualised representation of the Virgin’s death. The author bases this on the symbolic values of the boat and journey and on various other references from ancient culture and from the contemporary culture of the artist. The different elements, gestures and attitudes of the figures in the picture are also interpreted with a transcendentalism that lends them another significance. Lastly, a formal dependence is seen between this painting and other romantic works, especially the painting by Delacroix: The boat of Dante and Virgil.